(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This paper analyzes the opportunities and challenges in developing a sustainable blue economy in the Baltic Sea region, focusing primarily on clean technologies, renewable energy utilization, and circular material flows. The research methodology includes a comprehensive review of policy frameworks, technological innovations, and existing literature sourced from the Web of Science database, supplemented by bibliometric analysis to identify emerging trends and influential research. Results highlight significant environmental challenges such as pollution, overfishing, habitat degradation, and impacts from climate change. Despite these ecological threats, the findings reveal substantial economic growth opportunities through the adoption of sustainable practices. Critical factors identified for successful transition include effective resource management, technological innovation, and strengthened international collaboration. The study concludes that the Baltic Sea region has significant potential to become a global benchmark in sustainable marine and coastal resource management. Strategic recommendations emphasize the importance of enhancing policy support, fostering innovation, and promoting international cooperation to secure ecosystem preservation and economic resilience.